2018
DOI: 10.9755/ejfa.2018.v30.i1.1586
|View full text |Cite
|
Sign up to set email alerts
|

Azotochelin and N-dihydroxy-N,N’-diisopropylhexanediamide as Fe sources to cucumber plants in hydroponic cultures

Abstract: Environmental concerns related to the use of synthetic iron chelates, usually non-biodegradable, for overcoming iron chlorosis motivates the search for alternative compounds. Thus, the main aim of this work was to evaluate siderophore, azotochelin, and a siderophore mimic, N-dihydroxy-N,N’-diisopropylhexanediamide (DPH) as potential sources of iron to cucumber plants grown in hydroponic cultures. The behavior of the iron chelates of azotochelin and DPH, as a substrate of ferric chelate reductase (FCR) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…The results found for the SPAD of stage 2 leaves along the 21 days after the treatment ( Figure 3 ) are comparable to the SPAD data obtained by Martins et al (2018) and Ferreira et al (2019c) when synthetic siderophores [Fe(III)-azotochelin] or analogs thereof [Fe(III)- N , N ′-dihydroxy N , N ′diisopropylhexanediamide] chelates were tested as Fe sources to cucumber plants in hydroponic conditions and soybean ( G. max ) in calcareous soils, respectively. In addition, when examining the data from the SPAD of the 21 DAT ( Figure 4 ), it is possible to observe that, unless for o,o -EDDHA, all other treatments had shown a decrease in the effectiveness over time, in particular, B. subtilis ISS.…”
Section: Discussionsupporting
confidence: 80%
“…The results found for the SPAD of stage 2 leaves along the 21 days after the treatment ( Figure 3 ) are comparable to the SPAD data obtained by Martins et al (2018) and Ferreira et al (2019c) when synthetic siderophores [Fe(III)-azotochelin] or analogs thereof [Fe(III)- N , N ′-dihydroxy N , N ′diisopropylhexanediamide] chelates were tested as Fe sources to cucumber plants in hydroponic conditions and soybean ( G. max ) in calcareous soils, respectively. In addition, when examining the data from the SPAD of the 21 DAT ( Figure 4 ), it is possible to observe that, unless for o,o -EDDHA, all other treatments had shown a decrease in the effectiveness over time, in particular, B. subtilis ISS.…”
Section: Discussionsupporting
confidence: 80%
“…Synthetic N , N -dihydroxy- N , N ′-diisopropylhexanediamide (DPH), a hydroxamate, and Azotochelin, a catecholate, were used as controls (Martins et al 2018). As blank, 1.0 mL of deionised water was used in both assays.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that iron deficiency is a yield-limiting factor with major implications for crop management, the production of siderophores compounds is an important challenge. In recent works (Ferreira et al 2019a; Martins et al 2018), it was shown that synthetic compounds containing catecholate and hydroxamate groups are potential iron chelators for iron nutrition in plants. However, due to the high structural complexity of siderophores, its production by chemical synthesis involves several low yield steps, which limits the feasibility of their use for agriculture purposes, as it is illustrated in the synthesis of azotochelin (Leydier et al 2008; Martins et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Three bacterial species, Bacillus megaterium , B. subtilis , and A. vinelandii expressed the maximum iron-chelating capacity, suggesting their potential to help overcome the iron deficiency in plants ( Ferreira et al, 2019 ). Recent research described synthetic compounds, including catecholate and hydroxamate groups, as probable iron-chelating compounds that can provide nourishment and growth to plants ( Martins et al, 2018 ; Ferreira et al, 2019 ). The use of siderophores in agriculture is practically limited because of their complex structure and difficulty to produce owing to a multistep but low yielding process ( Leydier et al, 2008 ; Martins et al, 2018 ; Table 8 ).…”
Section: Introductionmentioning
confidence: 99%